2015
DOI: 10.1038/srep13107
|View full text |Cite
|
Sign up to set email alerts
|

Age-related profiling of DNA methylation in CD8+ T cells reveals changes in immune response and transcriptional regulator genes

Abstract: Human ageing affects the immune system resulting in an overall decline in immunocompetence. Although all immune cells are affected during aging, the functional capacity of T cells is most influenced and is linked to decreased responsiveness to infections and impaired differentiation. We studied age-related changes in DNA methylation and gene expression in CD4+ and CD8+ T cells from younger and older individuals. We observed marked difference between T cell subsets, with increased number of methylation changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 62 publications
5
125
0
Order By: Relevance
“…It is well-known that genome-wide decreases in the methylation of repetitive elements (particularly Alu sequences) and gene coding regions occur during aging (Bollati et al, 2009; Heyn et al, 2012; Salpea et al, 2012). These age-dependent DNA methylation changes also occur in immune-specific genes that contribute to T cell senescence (Shanley et al, 2009; Fernández-Morera et al, 2010; Hongdong et al, 2015; Tserel et al, 2015). …”
Section: Molecular Mechanisms Of T Cell Senescencementioning
confidence: 99%
“…It is well-known that genome-wide decreases in the methylation of repetitive elements (particularly Alu sequences) and gene coding regions occur during aging (Bollati et al, 2009; Heyn et al, 2012; Salpea et al, 2012). These age-dependent DNA methylation changes also occur in immune-specific genes that contribute to T cell senescence (Shanley et al, 2009; Fernández-Morera et al, 2010; Hongdong et al, 2015; Tserel et al, 2015). …”
Section: Molecular Mechanisms Of T Cell Senescencementioning
confidence: 99%
“…Second, epigenetic shifts are directional DNA methylation states at specific sites that seem to be stereotyped and age-specific across individuals. For example, methylation and chromatin accessibility of the genome organizer SATB1 is negatively correlated with age in T-cells[41], and genes used in autophagy are hypermethylated in aging macrophages[43]. Currently, the directness of the relationship between epigenetic marks and transcriptional outputs is still unclear.…”
Section: Metastability Of Aging Phenotypesmentioning
confidence: 99%
“…A study of CD8+ T lymphocytes from geriatric and young patients showed methylation status of T cells was significantly more variable in geriatric CD8+ T cells and this correlated with decreased immune function. Several genes important in CD8+ T cell differentiation and immune response, such as IFNy and CCL5, had decreased methylation which correlated with higher transcription levels[85]. These studies were confounded, however, by decreased naïve T cells and increased memory T cells in the older population, which could skew the methylation status data.…”
Section: Metabolism and Epigenetic Modifications In T Cellsmentioning
confidence: 99%